Familial deletion of the HOXA gene cluster associated with Hand–Foot–Genital syndrome and phenotypic variability. Issue 1 (20th September 2016) - Tas, Emir; Sebastian, Jessica; Madan‐Khetarpal, Suneeta; Sweet, Philip; Yatsenko, Alexander N.; Pollock, Nijole; Rajkovic, Aleksandar; Schneck, Francis X.; Yatsenko, Svetlana A.; Witchel, Selma Feldman
Abstract : Hand–Foot–Genital syndrome is a rare autosomal dominant condition characterized by distal limb anomalies and urogenital malformations. This disorder is associated with loss‐of‐function mutations in the HOXA13 gene. HOXA13 plays an important role in the development of distal limbs and lower genitourinary tract of the fetus. We report a novel familial 589 kb deletion in the 7p15.2 region identified in a male toddler and his mother. The proband had severe penoscrotal hypospadias, mild skeletal anomalies of the hands and feet, cardiac, renal, and gastrointestinal anomalies. His mother had a bicornuate uterus, cervical incompetence, and minor anomalies of her hands and feet. This family was found to have the smallest reported deletion of 7p15.2 to date, and presented with features typical of Hand–Foot–Genital syndrome in the mother, but much more severe phenotype in her son. This deletion included the entire HOXA cluster in addition to the SKAP2 and EVX1 genes. An RT‐PCR analysis was performed to determine the expression of the HOXA genes in the proband and to explore a parent‐of‐origin effect. Our expression studies did not support the hypothesis of an imprinted status of the HOXA2, HOXA3, HOXA5, and HOXA11 genes in peripheral blood. To our knowledge, this is the first familial 7p15.2 deletion. This family raises possibility for sexual dimorphism as a mechanism for phenotypic variability in patients with the HOXA gene cluster deletions. © 2016 Wiley Periodicals, Inc.